Optimizing the Role of the Family in Prevention Teen Smartphone Addiction through Psychoeducation Smartphone Addiction to Parents - Liza Marini*; Wiwin Hendriani; Primatia Yogi Wulandari (Universitas Lancang Kuning, 2023)
The use of smartphones is a major need at this time, especially for teenagers, but excessive use can have a negative impact, one of which is becoming addicted to smartphones. This is allegedly sourced from problems in the relationship between parents and children as well as the lack of warm communication in the family. This PkM aims to increase parent's comprehension of smartphone addiction in children, especially teenagers and to be able to describe the role of the family in preventing the emergence of smartphone addiction. This PkM activity uses the lecture method in the form of hybrid seminars (online and offline) providing psychoeducation to parents regarding early detection of smartphone addiction and optimizing the role of the family in preventing smartphone addiction in adolescents accompanied by questions and answers, and evaluation. The results showed that there was an increase in parental knowledge in the very good and good (52%) and sufficient (24%) categories. Optimizing the role of the family, in this case, parents as educators, helps maximize the relationship and communication between parents and children to prevent smartphone addiction in adolescents.